PENGARUH KEPUASAN KERJA, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI RUMAH SAKIT - Muhammad Rasyid Asy-Syifa; Fatmah Bagis; Wida Purwidianti; Purnadi Purnadi (JURNAL ILMIAH EDUNOMIKA, 2024)
The aims of this research is to investigate the effect among job satisfaction, organizational culture, and employee performance at hospital, involving the entire staff of the hospital. Through the application of a Non-probability technique, specifically employing the purposive sampling method, a research sample of 105 respondents who met specific criteria was selected. The data collection process entailed the distribution of a questionnaire. The purposive sampling method was deliberately utilized to guarantee that participants fulfilled predetermined criteria. The analysis of the collected data employed Partial Least Square (PLS) analysis. The results of the analysis reveal that job satisfaction significantly and positively impacts employee performance. Furthermore, organizational culture is determined to have a noteworthy positive influence on employee performance. Additionally, work discipline is recognized as having a significant positive effect on employee performance.